Social Media and Customers Purchasing Decision - Pokharel, Santosh; Luitel, Madan Kumar; Ravi, Jaladi (DEPAN, 2025)
Business advertisement in social media has risen these days. The main objective of this research is to analyze the effect of social media in purchasing decision making of customer. The survey was conducted to study the social media impact among different age group around the Kathmandu valley. This survey focused on various factors that are considered by the customer while making purchase from any social media. The findings of this research are the impact of social media marketing in different age group of male and female. Although it is usually perceived that the price, return policy, cash on delivery, cash back warranty, business reputation and trust are the influencing factor for making purchase from social media which also varies among different age groups. Another is the online purchasing has significant relation with the genders of customer. It has been found that there is a significant difference in male and female for the use of social media platform but that was insignificant for taking attention on the advertisement on social media.